Hubungan Terapi Meditasi Dengan Kecemasan Menghadapi Persalinan - anisa wigati rozifa (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Objective: Labor pain is a natural process that, if not handled properly, will cause problems such as increased anxiety during labor. Several methods to reduce pain in delivery include pharmacological and non-pharmacological approaches. One of the non-pharmacological methods that are effective in reducing pain is meditation. The purpose of this study was to analyse the relationship between meditation and anxiety levels in dealing with childbirth.Methods: The design of this study used a descriptive-analytic research design. This study used the research subjects of third-trimester primigravida pregnant women who meditated and did not meditate at RSI Darus Syifa' Surabaya. Sample selection using purposive sampling technique following the inclusion and exclusion criteria that have been determined.Results: The results showed that the mother's occupation had a significant relationship with the level of anxiety in the face of childbirth, namely p <0.05. Meanwhile, the education category did not have a significant relationship with anxiety in the face of delivery with p>0.05. The characteristic relationship between doing and not doing meditation in primigravida showed a significant relationship between age, occupation, and meditation (p<0.05). Education level has no meaningful relationship with meditation.Conclusion: This study concludes a significant relationship between maternal characteristics (age and occupation) and meditation in primigravida. However, education does not have a significant relationship with meditation in primigravida. There is a strong relationship between the level of anxiety in the face of labor between those who do and do not meditate in primigravida